Can Breast Tumors Affect the Oxidative Status of the Surrounding Environment? A Comparative Analysis among Cancerous Breast, Mammary Adjacent Tissue, and Plasma. (30th November 2015) - Panis, C.; Victorino, V. J.; Herrera, A. C. S. A.; Cecchini, A. L.; Simão, A. N. C.; Tomita, L. Y.; Cecchini, R.
Abstract : In this paper, we investigated the oxidative profile of breast tumors in comparison with their normal adjacent breast tissue. Our study indicates that breast tumors present enhanced oxidative/nitrosative stress, with concomitant augmented antioxidant capacity when compared to the adjacent normal breast. These data indicate that breast cancers may be responsible for the induction of a prooxidant environment in the mammary gland, in association with enhanced TNF- α and nitric oxide.